A Generic Construction of Accountable Decryption and Its Applications - ZHOU, Xuhua (Institutional Knowledge at Singapore Management University, 2012)
We propose a new cryptographic notion called accountable decryption by which, given a ciphertext, a decryptor proves both the correctness of his decryption and the plaintext authenticity to a public verifier. We define its security from three aspects: message confidentiality, soundness of verifiability and plaintext authenticity. Given any asymmetric or symmetric key encryption scheme, we propose a method to construct the corresponding accountable decryption scheme with provable security. To demonstrate its applications, we also present the constructions for predicate encryption and for public-key encryption with keyword search.